2021
DOI: 10.1111/cts.13174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal impairment on the pharmacokinetics and safety of dorzagliatin, a novel dual‐acting glucokinase activator

Abstract: Dorzagliatin is a novel allosteric glucokinase activator targeting both pancreatic and hepatic glucokinase currently under clinical investigation for treatment of type 2 diabetes (T2D). This study aimed to investigate the effect of renal impairment (RI) on dorzagliatin’s pharmacokinetics (PKs) and safety, and to guide appropriate clinical dosing in patients with diabetic kidney disease, including end‐stage renal disease (ESRD). Based on the results from physiologically‐based pharmacokinetic modeling, the predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Dorzagliatin was also studied in a population with end-stage renal disease and a healthy control group to evaluate the effect of renal impairment on pharmacokinetics and safety. The results suggested that dorzagliatin can be safely used in patients with T2D at all stages of renal impairment without a need for dose adjustment 58 .…”
Section: Any Hypoglycemiamentioning
confidence: 93%
“…Dorzagliatin was also studied in a population with end-stage renal disease and a healthy control group to evaluate the effect of renal impairment on pharmacokinetics and safety. The results suggested that dorzagliatin can be safely used in patients with T2D at all stages of renal impairment without a need for dose adjustment 58 .…”
Section: Any Hypoglycemiamentioning
confidence: 93%
“…Whereas, this study confirmed that dorzagliatin triggered only 0.7 and 0.4% of drug-related hypoglycemia and hyperlipidemia, suggesting that dorzagliatin does not significantly increase the incidence of hypoglycemia and hyperlipidemia. In addition, meta-analysis confirmed that dorzagliatin does not increase serious AEs and related studies showed that dorzagliatin can be used in patients with T2DM at all stages of renal impairment (12,45), which implies that dorzagliatin has a good safety profile.…”
Section: Discussionmentioning
confidence: 81%
“…The recommended dosage of dorzagliatin is one 75 mg oral tablet twice daily, 1 h before breakfast and dinner. No dosage modification is necessary for patients with T2D and chronic kidney disease 48,49 …”
Section: Clinical Exploration On Gk Targetmentioning
confidence: 99%